The use of technical ceramics in early Egyptian glass-making - M. Smirniou (19730740) (2016)
We present a detailed description of the layered structure developing in the walls of Egyptian Late Bronze Age glass-making vessels, and in similar vessels successfully replicated in laboratory experiments. The analyses show that this layered discolouration and change in ceramic composition is due to the interaction of the glass batch with the vessel during firing. The formation of this visually striking and easy to recognise pattern is due to the chloride content of primary glass batches and does not occur in vessels used to re-melt existing glass. Thus, we argue that these discolourations can be used as a reliable and easy field guide to identify glassmaking waste among Late Bronze Age ceramic assemblages, hopefully increasing the currently very small number of identified LBA glassmaking workshops. Other Information Published in: Journal of Archaeological Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jas.2016.01.009